Retributive Whisper: Communicative Elements in Parole. Issue 3 (25th June 2014) - Dagan, Netanel; Segev, Dana
<x xml:space="preserve">Abstract</x> The aims of retributive or nonutilitarian sentencing are said to conflict with parole as part of a determinate sentencing framework. In this article, we claim that a nonutilitarian approach to punishment does not necessarily conflict with parole. In particular, by adopting core elements of Duff's framework of communicative sentencing, we argue that parole inherently holds a communicative meaning in the form of retributive whisper and can thus be reconciled with a nonutilitarian approach to punishment. In addition, we explore a way to enhance the communicative potential in the parole process and suggest that by recognizing and further incorporating the inherent communicative message in parole we can increase or maximize the board's communicative potential. Finally, we discuss some benefits that can emerge from adapting a communicative sentencing framework to the parole process.